(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article studies the quality of contentment in the poet’s epic “Hayrat ulAbror”, this quality is interpreted as the quality of perfection, and in the process of comparing it with the quality of patience, the interpretation of contentment in “Mahbub ul-Qulub” is also analyzed. In this way, it is highlighted that the issue of satisfaction and patience is highlighted as one of the conditions for achieving perfection in the work of the poet. By revealing the essence of the story in the work, the evil of people’s cupidity and the virtue of living contentedly in this world are revealed in contrast. The article explains that the idea of being patient is still relevant today and the importance of perfect human education